Antifungal activity of Bacillus subtilis subsp. spizizenii BL-59 to control some important postharvest diseases of mango fruits (Mangifera indica L.) - Duangkaew, P.; Monkhung, S. (International Journal of Agricultural Technology, 2021)
The antifungal activity of antagonistic bacteria isolated from the rhizosphere soil of rice in Ban-Laem district, Phetchaburi province, Thailand was investigated. The fungal pathogens, Colletotrichum sp. and Pestalotiopsis sp. were isolated from the infected fruit, causing postharvest diseases in mango. The preliminary study was conducted using a dual culture assay to determine the antifungal activity of the BL-59 isolate. The dual culture assay showed that the antagonistic bacteria inhibited the mycelial growth of Colletotrichum sp. and Pestalotiopsis sp. by 49.31% and 42.55%, respectively. Furthermore, this isolate BL-59 produced volatile organic compounds (VOCs), which inhibited the mycelial growth of Colletotrichum sp. by 60.00%. Microscopic observation of the hyphal morphology of Colletotrichum sp. revealed the presence of abnormal hyphal structure. Morphological and biochemical studies of antagonistic bacteria BL-59 demonstrated that this isolate was classified as gram-positive, rod-shaped, and endospore-forming, and it showed survival growth under salinity stress and high temperature (45ºC). Moreover, this strain produced catalase and oxidase enzymes. BL-59 was identified as closely related to Bacillus subtilis subsp. spizizenii (99.79%) using molecular identification based on the 16S rRNA gene. This study revealed that antagonistic bacteria can be used as an alternative choice to control anthracnose disease by reducing the chemical residues in agricultural production